Management and Processing of Waste Generated In UTP Cafeterias - Gulwa, Mzolisi (Universiti Teknologi PETRONAS, 2008)
Management and processing of waste is motivated by concern for public health in this case the public being the community of UTP. The problem of waste management at the university is evident from the stagnant dirty water (which is direct result food waste) found in the open channels that come from the cafeterias. This raises concerns about the health and aesthetics of the campus and this is a problem that needs a solution. The management and processing of waste generated at canteens was tried to be solved by application of the composting process. The waste was collected from the busiest and biggest canteen (village four) on campus. After the collection it was transported to the com posting site behind block 13 for the start of the com posting. The waste generated at these canteens consists of food waste, plastics, cardboards, tins and cans. Their compositions by percentage weight are 69, 14, 9 and 8% respectively. Food waste contains the most energy with a value of 137 667.9 kJ daily and the total energy that can be recovered amounts to 445 344.9 kJ. Yard waste is one of the largest wastes generated at UTP and it was used mainly to adjust the C/N ratio by providing a high carbon concentration to balance nitrogen rich food waste. Sludge is also used in some of the experimental runs as way to determine if the introduction of microorganisms has an etTect compared to naturally occurring composting. The parameters used to monitor the process were moisture content, temperature, pH and C/N ratio. Eight different batches consisting of different compositions of feedstock were used in order to find the right mixture of the feedstock which will be recommended for the actual processing of the waste. Four of these eight bathes commenced naturally and in the other four microbes was introduced in the form sludge. pH f1uctuated around the neutral value for almost all the batches. Batches with bigger percentage of yard waste were poor in maintaining any moisture and the more food waste a batch contained the better in maintaining the moisture. Temperature was not a useful parameter as it did not deviate much around the surrounding environment temperature of 28°C. A tier seven weeks it was that the addition of sludge had no effect in the process. After comparing the batches' physical characteristics batch C (food waste: 60%, yard waste: 40%) was the best performing batch with batch A (I 00% food waste) being the worst performing batch.